Agrobacterium-Mediated Transformation for the Development of Transgenic Crops; Present and Future Prospects - Rahman, Saleem Ur; Khan, Muhammad Omar; Ullah, Rahim; Ahmad, Fayaz; Raza, Ghulam (Molecular biotechnology, 2024)
Plant transformation based on Agrobacterium- mediated transformation is a technique that mimics the natural agrobacterium system for gene(s) introduction into crops. Through this technique, various crop species have been improved/modified for different trait/s, showing a successful genetic transformation so far. This technique has many advantages over other transformation methods such as stable integration of transgene, cost effective. However, there are many limitations of this technology such as mostly the crops are recalcitrant to agrobacterium, low transformation efficiency, transgene integration as well as off targets. So, it’s very important to explore the major limitations and possible solutions for Agrobacterium- mediated transformation in order to increase its genetic transformation efficiency. Therefore, the present review article gives a comprehensive study how the transgenic crops are developed using Agrobacterium -mediated transformation, crops that have already been modified through this method, and risks associated with transgenic plants based on Agrobacterium- mediated transformation. Moreover, the challenges and problems associated with Agrobacterium -mediated transformation and how those problems can be solved in future for a successful genetic transformation of crops using modern biotechnology techniques such as CRISPR/Cas9 systems. The present review article will be really helpful for the audience those working on Genome editing of crops using Agrobacterium- mediated transformation and will opens many ways for future plant genetic transformation.